2014
DOI: 10.1007/s13197-014-1341-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber fractions of prickly pear cactus (nopal) on quality and sensory properties of wheat bread rolls

Abstract: In this study the addition of total fiber (TF), insoluble fiber (IF), and soluble fiber (SF) from nopal to wheat flour used to make bread rolls was assessed. The rheological properties of dough as well as quality, texture, sensorial and physical characteristics of the crumb rolls produced were evaluated. The storage (23.50 MPa) and loss modulus (11.95 MPa) for SF-dough were the lowest indicating that a less visco-elastic behavior was obtained. Polarized light microscopy showed that a more homogeneous size and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…A result of 60.73 ± 0.008 in L*, −6.513 ± 0.004 in a* and a value of 28.55 ± 0.02 in b* was obtained, which indicates that the NF is pale green with a high luminosity, characteristic colors of this raw material. Chávez-Gonzalez [ 12 ] and Guevara-Arauza [ 15 ] determined the color in nopal flour and obtained results similar to those mentioned, where he reported that the color of the flour is not very intense and changes easily with the addition of natural colors or when other products are added to consume like desserts and cookies.…”
Section: Resultsmentioning
confidence: 66%
“…A result of 60.73 ± 0.008 in L*, −6.513 ± 0.004 in a* and a value of 28.55 ± 0.02 in b* was obtained, which indicates that the NF is pale green with a high luminosity, characteristic colors of this raw material. Chávez-Gonzalez [ 12 ] and Guevara-Arauza [ 15 ] determined the color in nopal flour and obtained results similar to those mentioned, where he reported that the color of the flour is not very intense and changes easily with the addition of natural colors or when other products are added to consume like desserts and cookies.…”
Section: Resultsmentioning
confidence: 66%
“…Increase in these values with incremental replacement of FC is expected due to dilution of gluten matrix and increased fibre content. Crumb springiness, a value describing the recovery of the sample after compression, is important in separating soft, soggy crumb from soft but resilient crumb (Guevara-Arauza et al., 2014). In comparison with control, springiness value for bread supplemented with 2% FC was constant, indicating that the addition of 2% fibre to the recipe did not show a significant effect on this attribute.…”
Section: Resultsmentioning
confidence: 99%
“…The operating conditions of the instrument were as follows: 2 mm/s pre-test speed, 2 mm/s test speed, 2 mm/s post-test speed, 0.10 N trigger force and 10 mm distance of penetration and 60 s time of compression. The parameters recorded were: hardness (N): first peak in Texture Profile Analysis (TPA) analysis; cohesiveness is the area of work during the second compression divided by the area of work during the first compression (dimensionless); springiness (dimensionless) is measured by the distance of the detected height during the second compression divided by the original compression distance; and chewiness (N) the product of hardness, cohesiveness and springiness, gives an indication of the energy required to masticate a solid food (Guevara-Arauza et al., 2014). Change in hardness during storage was used as a parameter to evaluate bread staling.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al (2002) used carob fiber, inulin and pea fiber as fiber-enriching agents in bread making. Furthermore, many forms of dietary fiber have been used in bakery products such as rice bran (Abdul-Hamid and Luan 2000), potato fiber (Kaack et al 2006) and pear cactus fiber (Guevara-Arauza et al 2014). However, relatively less research was conducted on the effects of different dietary fiber addition on cake quality characteristics (Sudha et al 2007;Gularte et al 2012).…”
Section: Introductionmentioning
confidence: 99%